Al‐Doping‐Induced VO2 (B) Phase in VO2 (M) Toward Smart Optical Thin Films with Modulated ΔTvis and ΔTc. Issue 12 (16th October 2019) - Wang, Shuxia; Wei, Wei; Huang, Tiantian; Yuan, Menghui; Yang, Yan; Yang, Wanli; Zhang, Rui; Zhang, Tianning; Chen, Zhimin; Chen, Xin; Shen, Guozhen; Dai, Ning
Abstract : Vanadium dioxide (VO2 ) thin films are among the promising candidates for smart optical materials and energy‐saving devices with a metal–insulator transition (MIT) near room temperature. The modulation of hysteresis width (Δ T c ) and optical characteristics of the solar spectral band ( T sol ) during the MIT of vanadium oxides used for thermochromic devices is still challenging. In this article, we describe Al‐doped VO2 thin films with modulated visible spectral band ( T vis ) and Δ T c . The control of the Al/V ratio and Al‐doping‐induced VO2 (B) phases in VO2 is achieved by combining atomic layer deposition and post‐annealing processes. With increasing Al/V ratio, the content of VO2 (B) phases increases in VO2 (M). Δ T vis, Δ T c, and Al‐doping‐induced VO2 (B) phases are found to be dependent on the aluminum content in thin films. Δ T vis up to 21.18% and Δ T c down to 3.3 K for Al‐doped VO2 may be attributed to the coordinated interaction of both Al doping and the VO2 (B) phases in the VO2 matrix during MIT. These modulations may allow an understanding of the essential physics behind the MIT of doped VO2 and thus fabrication of smart optical sensors, energy‐saving devices, and even ultrafast Mott transistors. Abstract : Metal–insulator transition (MIT) hysteresis and optical characteristics are modulated in Al‐doped VO2 thin films. The coordinate interaction of Al‐doping and VO2 (B) phases determines infrared and visible transmissivity (Δ T vis ) and hysteresis width (Δ T c ) during MIT. Such modulation allows an understanding of the underlying physics behind the MIT of doped VO2 and construction of smart optical devices.